2018
DOI: 10.1017/wsc.2017.76
|View full text |Cite
|
Sign up to set email alerts
|

Weed Communities in Semiarid Rainfed Croplands of Central Argentina: Comparison between Corn (Zea mays) and Soybean (Glycine max) Crops

Abstract: The semiarid Espinal in central Argentina, being recently transformed from natural semiarid grasslands into agriculture, represents an interesting scenario to understand the early stages of weed community assembly and its relationship with crop identity and management. Our aim was to characterize the weed communities in corn (Zea maysL.) and soybean [Glycine max(L.) Merr.], the main crops of the Espinal region, under the dominant rainfed conditions. Weed surveys were carried out in 53 fields, and farmers were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 42 publications
0
11
0
1
Order By: Relevance
“…The highest RF% of weeds in the second and third sowing times was found with the BMX-TornadoRR cultivar (Table 3). (Kamoshita et al, 2014;Pinke et al, 2016;Rauber et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…The highest RF% of weeds in the second and third sowing times was found with the BMX-TornadoRR cultivar (Table 3). (Kamoshita et al, 2014;Pinke et al, 2016;Rauber et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Despite, a total of 12 environmental variables were included in the analysis, only the above three variables were significant in the regression model. The possible justification is that the environmental variables are not the only factors controlling the weeds communities in citrus farms as reported on other agroecosystems (see Rauber et al, 2018). Other biotic interaction may contribute in structuring the weeds communities in agroecosystems.…”
Section: Discussionmentioning
confidence: 97%
“…However, Fried et al (2008) found that the soil pH and soil texture are the most important factors structuring the weed communities in temperate region (France). On the other hand, some studies highlighted the agricultural practices are the main driver for diversity and abundance of weeds in agroecosystems (Rauber et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Dalian is a coastal city, which is affected by the continental monsoon and marine climate. Therefore, it is of great significance to analyze the 50 year precipitation law of four stations for understanding the precipitation cycle change law in the semi-arid area of northern China under the background of global change (Rauber et al, 2018).…”
Section: Data Sources and Methodsmentioning
confidence: 99%